Anisotropic Rod‐Shaped Particles Influence Injectable Granular Hydrogel Properties and Cell Invasion. Issue 12 (24th January 2022) - Qazi, Taimoor H.; Wu, Jingyu; Muir, Victoria G.; Weintraub, Shoshana; Gullbrand, Sarah E.; Lee, Daeyeon; Issadore, David; Burdick, Jason A.
Abstract: Granular hydrogels have emerged as a new class of injectable and porous biomaterials that improve integration with host tissue when compared to solid hydrogels. Granular hydrogels are typically prepared using spherical particles and this study considers whether particle shape (i.e., isotropic spheres vs anisotropic rods) influences granular hydrogel properties and cellular invasion. Simulations predict that anisotropic rods influence pore shape and interconnectivity, as well as bead transport through granular assemblies. Photo‐cross‐linkable norbornene‐modified hyaluronic acid is used to produce spherical and rod‐shaped particles using microfluidic droplet generators and formed into shear‐thinning and self‐healing granular hydrogels, with particle shape influencing mechanics and injectability. Rod‐shaped particles form granular hydrogels that have anisotropic and interconnected pores, with pore size and number influenced by particle shape and degree of packing. Robust in vitro sprouting of endothelial cells from embedded cellular spheroids is observed with rod‐shaped particles, including higher sprouting densities and sprout lengths when compared to hydrogels with spherical particles. Cell and vessel invasion into granular hydrogels when injected subcutaneously in vivo are significantly greater with rod‐shaped particles, whereas a gradient of cellularity is observed with spherical particles. Overall, this work demonstrates potentially superior functional properties of granular hydrogels with rod‐shaped particles for tissue repair. Abstract : Spherical and rod‐shaped microparticles are fabricated using droplet microfluidics and assembled into injectable and porous granular hydrogels for tissue repair. Changing particle shape improves structural features such as pore anisotropy and increases bulk mechanics such as storage moduli. Hydrogels containing rod‐shaped particles support robust endothelial cell sprouting in vitro and uninhibited cell invasion in vivo.